2016
DOI: 10.1093/nar/gkw615
|View full text |Cite
|
Sign up to set email alerts
|

Human CDK18 promotes replication stress signaling and genome stability

Abstract: Cyclin-dependent kinases (CDKs) coordinate cell cycle checkpoints with DNA repair mechanisms that together maintain genome stability. However, the myriad mechanisms that can give rise to genome instability are still to be fully elucidated. Here, we identify CDK18 (PCTAIRE 3) as a novel regulator of genome stability, and show that depletion of CDK18 causes an increase in endogenous DNA damage and chromosomal abnormalities. CDK18-depleted cells accumulate in early S-phase, exhibiting retarded replication fork ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 57 publications
7
40
0
Order By: Relevance
“…Dysregulation of CDKs results in imbalance in apoptosis and proliferation which is a hallmark of a cancer. Loss of CDK18 may lead to dysregulation of cell-cycle check-point increasing genomic instability and development of gastric cancer [ 32 ]. Another gene that was related to GC identified in this study is PR domain containing 16 ( PRDM16 ) which is function as a zinc finger transcription factor regulates chromatin function and different transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of CDKs results in imbalance in apoptosis and proliferation which is a hallmark of a cancer. Loss of CDK18 may lead to dysregulation of cell-cycle check-point increasing genomic instability and development of gastric cancer [ 32 ]. Another gene that was related to GC identified in this study is PR domain containing 16 ( PRDM16 ) which is function as a zinc finger transcription factor regulates chromatin function and different transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we aimed to characterize its function in the regulation of AQP2. It has been shown that CDK18 may be involved in Alzheimer's disease, [50,51] in the Ataxia Telangiectasia and RAD3-related (ATR)-mediated response to single strand DNA and in cell cycle control [52,53]. Indeed, its role in cell cycle control is in line with the by 30% reduced MCD4 cell number if CDK18 was knocked down ( Table 1).…”
Section: Knockdown Of Cdk18 Inhibits the Camp-induced Redistributionmentioning
confidence: 90%
“…It is expressed in neuronal tissue and there is evidence that it plays a role in the progression of Alzheimer's disease, since it is found in high concentrations in pathological tissue, and is proposed to modulate Tau phosphorylation (Herskovits and Davies 2006). More recently, it has been shown to prevent accumulated DNA damage and genome instability in response to replication stress (Barone et al 2016).…”
Section: Discussionmentioning
confidence: 99%